Reconstruction of Qiyas Al-Nahwi in Ta'rib: A Comparative Study of Classical and Contemporary Scholars' Thoughts on The Formation of Arabic Terms - Kozin; Rihlah Ilmiah (Mimbar Agama Budaya, 2025)
Qiyas appears as an intellectual method that operates in several fields at once: usul fiqh, nahwu, and modern linguistics, in which process it has undergone a shift in orientation from a relatively closed normative model to a more creative model that is more adaptive to contemporary socio-linguistic changes. Challenges Industrial development, globalization, and technology have made the role of ta'rib (Arabization) crucial as a process of incorporating foreign words or new concepts into Arabic through qiyas nahwi. This study focuses on the dynamics of qiyas according to classical and contemporary linguists and discusses qiyas patterns and what needs to be used as a reference in developing qiyas as a means of ta'rib. The results of this study indicate that the orientation of qiyas by Nahwu scholars emphasizes the preservation of language purity by generalizing from selected fasih kalām, thus tending to reject syādz forms as aṣl and limiting linguistic creativity. Meanwhile, in modern linguistics and Majma‘ practice, the challenges of the times demand openness and new rules that are more flexible, open, and applicable. The reconstruction of qiyas in contemporary ta'rib has four main points: the purpose of qiyas is directed at maintaining the vitality and expressive power of fusha as the language of science and civilization; sources are canonical and innovative; the inclusion of modern elements that are already stable in the pillars; and the role of authoritative institutions and popularity in the operation of ta'rib.